Influence of Antiplatelet Drugs in the Pathogenesis of Experimental Periodontitis and Periodontal Repair in Rats - Coimbra, Leila S. [UNESP]; Rossa, Carlos [UNESP]; Guimaraes, Morgana R. [UNESP]; Gerlach, Raquel F.; Muscara, Marcelo N.; Spolidorio, Denise M. P. [UNESP]; Herrera, Bruno S. [UNESP]; Spolidório, Luis Carlos [UNESP] (Amer Acad Periodontology, 2011)
Background: Platelets contain an array of biologic mediators that can modulate inflammation and repair processes including proinflammatory mediators and growth factors. Previous studies have shown that periodontitis and periodontal repair are associated with platelet activation. We hypothesized that drug-induced platelet inactivation may interfere in the processes of inflammation and repair in experimental periodontitis in rats by suppressing the release of biologic mediators from platelets to the site of injury.Methods: To measure the effects on periodontitis, ligatures were placed around first molars, and aspirin (Asp, 30 mg/kg) or clopidogrel (Clo, 75 mg/kg) was given intragastrically once daily for 15 days. Interleukin-6 (IL-6), tumor necrosis factor-a (TNF-alpha), and thromboxane A(2) levels were measured by enzyme-linked immunosorbent assay. To evaluate the effects of antiplatelet drugs on periodontal repair, ligatures were removed after 15 days of periodontitis induction, and Asp or Clo were administered beginning the following day for 15 days. Periodontal repair was assessed by microcomputed tomography.Results: on periodontitis phase, Asp and Clo significantly reduced levels of TNF-alpha and II-6 (P < 0.05), but only Asp decreased thromboxane A(2) (P < 0.05). Asp and Clo decreased inflammatory infiltration; however, this reduction was more pronounced with Clo treatment (P < 0.05). Histometric analysis showed that Asp and Clo impaired alveolar bone resorption. During the repair phase and after removal of the ligatures, microcomputed tomography analysis demonstrated that treatment with Asp and Clo did not impair alveolar bone repair.Conclusion: Systemic administration of Asp and Clo attenuates the inflammation associated with periodontitis without affecting the repair process when stimulus is removed. J Periodontol 2011;82:767-777.
Keywords: Aspirin; blood platelets; clopidogrel; mediators of inflammation; periodontitis; platelet aggregation inhibitors